Long-term Tillage and Nitrogen Fertilization Effects on Soil Properties and Crop Yields - Muhajir Utomo; Irwan Sukri Banuwa; Henrie Buchari; Yunita Anggraini; . Berthiria (UNIVERSITY OF LAMPUNG, 2013)
The impact of agricultural intensification on soil degradation now is occurring in tropical countries. The objective of this study was to determine the effect of long-term tillage and N fertilization on soil properties and crop yields in corn-soybean rotation. This long-term study which initiated since 1987 was carried out on a Typic Fragiudult soil at Politeknik Negeri Lampung, Sumatra (105o13’45.5